RUSSIAN CLASSICAL TRADITION AND THE FORMATION OF RUSSIAN-LANGUAGE POETRY IN UZBEKISTAN IN THE TWENTY FIRST CENTURY - Yuldasheva Lola Kuldashevna (Modern American Journals, 2026)
This article examines the current state of contemporary Russian-language poetry in Central Asia, with particular attention to Uzbek poetry. One of the key factors shaping this phenomenon is the socio-aesthetic objectives of modern literature. The interaction between two literary traditions, which is central to the author’s research, has been addressed in contemporary scholarship and is closely connected to the issue of bilingualism. This issue has acquired significant social relevance, as it determines the processes of mutual enrichment between literatures. The study also demonstrates how the convergence or opposition of two literary systems—national and Russian—results in the formation of a distinctive cultural synthesis endowed with specific aesthetic qualities. The research provides detailed theoretical and practical insights into the mechanisms of literary bilingualism and the stylistic evolution of Russian-language poetry in Uzbekistan.
Keywords: Literary interaction; bilingualism; literary perception; cultural synthesis; Russian-language poetry.